SLEEP QUALITY AND STRUCTURE ASSESSMENT IN CHILDREN WITH PATHOLOGY OF ENT-ORGANS, BRONCHIAL ASTHMA AND THE MOST WIDESPREAD NERVOUS SYSTEM DISEASES - E. A. Abashidze; L. S. Namazova-Baranova; O. V. Kozhevnikova; V. V. Altunin; A. K. Gevorkyan (Union of pediatricians of Russia, 2013)
At present ca. 25% of children have sleep disorders. The main method of diagnosing sleep disorders is polysomnography. The article presents the analysis of night sleep study results in children with various pathologies. The study involved 103 children in total; 13 of them formed the control group. It is necessary to conduct a complex examination of sleep-wake cycle disorders involving a quantitative assessment of subjective complaints using a questionnaire and objective polysomnographic registration of night sleep parameters.